PENGARUH PERSEPSI KEMUDAHAN, PERSEPSI MANFAAT, DAN KEPERCAYAAN TERHADAP MINAT MENGGUNAKAN BANK DIGITAL SEABANK PADA GENERASI Z DAN MILENIAL - Dhiza Ganniessya Magandi; Rizki Pratomo Sunarwibowo (Nirta Learning Centre, 2026)
This study aims to examine the effect of perceived ease of use, perceived usefulness, and trust on the intention to use SeaBank digital banking among Generation Z and Millennials in Ciledug, Tangerang. Data were collected through the distribution of questionnaires to 398 respondents; however, only 338 respondents met the criteria as active SeaBank users and were therefore included as the research sample. The data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software version 4.1.1.6. The results indicate that perceived ease of use and perceived usefulness have a positive and significant effect on the intention to use SeaBank digital banking. In addition, perceived ease of use and perceived usefulness also have a positive and significant effect on trust. Furthermore, trust has a positive and significant effect on the intention to use. The results of the indirect effect analysis show that trust is able to mediate the relationship between perceived ease of use and perceived usefulness and the intention to use in a positive and significant manner. Overall, the findings confirm that ease of use, perceived benefits, and trust are important factors in shaping the intention of Generation Z and Millennials to use SeaBank digital banking services.